1998
DOI: 10.2116/analsci.14.343
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Cobalt in Natural Water as a 2-(5-Bromo-2-pyridylazo)-5-[N-propyl-N-(3-sulfopropyl)amino]phenol Chelate by On-Line Preconcentration HPLC with Column-Switching Technique

Abstract: Reversed-phase high performance liquid chromatography (RP-HPLC) with precolumn derivatization is a powerful method for the determination of trace amounts of metal ion because of its high sensitivity, simplicity, and low cost.1 However, some trace metal ions in natural water could not be determined by RP-HPLC directly. Combining with a suitable preconcentration technique is one of the effective ways to solve the problem.A solvent extraction 2-18 has been used commonly as the preconcentration technique for RP-HP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…8,21 A complemental study revealed that cobalt(II) ions are not retained in a column loaded with TAC in the presence of reducing agents, such as ascorbic acid and hydroxylammonium chloride. In aqueous solution the cobalt(III) complex has green coloration and an absorption maximum at 576 nm.…”
Section: Complex Formation Studiesmentioning
confidence: 99%
“…8,21 A complemental study revealed that cobalt(II) ions are not retained in a column loaded with TAC in the presence of reducing agents, such as ascorbic acid and hydroxylammonium chloride. In aqueous solution the cobalt(III) complex has green coloration and an absorption maximum at 576 nm.…”
Section: Complex Formation Studiesmentioning
confidence: 99%
“…But, separation and simultaneous determination of mixtures of metal ions as their metal-chelates with an organic chelating reagent by reversed-phase high-performance liquid chromatography (RP-HPLC) had been accepted in inorganic analysis in recent years. [4][5][6][7][8] The organic chelating reagents, were 4-(2-pyridylazo)-resorcinol(PAR), 8,9 4-(2-thiazolylazo)-resorcinol (TAR), 4,7 2-(2-thiazolylazo)-p-cresol(TAC), 10 1-oxa-4,7,10,13-tetraazacyclopentadecane (OTAP), 11 and 2-(5-bromo-2-pyridylazo)-5-[N-propyl-N-(3-sulfopropyl)amino]phenol (5BrPSAA), 5 etc. TAR is the one of the popular chelating reagents.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7][8][9][10] Moreover, reversed-phase high-performance liquid chromatography (RP-HPLC) with precolumn derivatization is a powerful method for the determination of trace amounts of metal ions, because of its high sensitivity. [11][12][13][14][15][16][17] However, the concentration of some metal ions in water samples, such as rain, marine and tap water, are generally too low to be determined directly by RP-HPLC. [18][19][20] On the other hand, an ion-pair RP-HPLC using a counter cation has, also, usually been employed for the separation and determination of metal chelates.…”
Section: Introductionmentioning
confidence: 99%